Swords, oaths, and prophetic visions : authoring warrior rule in medieval Japan - Oyler, Elizabeth, 1966- (Book collections on Project MUSE., 2006)
"Swords, Oaths, and Prophetic Visions investigates some of the most historically important political issues raised by the Genpei War (1180-1185). This epic civil conflict, which ushered in Japan's age of warriors, is most famously articulated in the monumental narrative Heike monogatari (The Tale of the Heike). Elizabeth Oyler's work lays out the complex interconnections between the numerous variant texts of the Heike and the historical events they describe. But Oyler's methodology also brings other texts and genres - the Gikeiki, the Soga monogatari, the Azuma kagami, and pieces from the kowakamai repertoire - into the picture. Rather than concentrating on individual texts, Oyler focuses on the manifold intertextual relationships within this larger body of narrative and drama and the collective role of these works in creating and disseminating stories about some of the Genpei War's most contentious events. In so doing, she works toward a new understanding of the underlying cultural problems of which these tales are symptomatic and which they attempt to address."--Jacket